The Importance of Focus and Auftakt Movements in Conducting Techniques - D. Raimova (Researchparks Publishing, 2021)
The article emphasizes the importance of attention and auftact in mastering the technique of conducting. At the beginning of the work on the selected work, the conductor must attract attention and acquire the ability to manage the team. To show the point of attention, it is important to analyze the piece and start with the conductor's apparatus and hands-on position. The auftact is also a gesture that rises above the point of attention. It is emphasized that the beginning of conducting is a movement capable of showing correct breathing, revealing the tempo and character of the work being studied.